Reinvigorating Growth in Developing Countries : Lessons from Adjustment Policies in Eight Economies - Kochhar, Kalpana (Occasional Papers; Occasional Paper ;, 1996)
This study examines the links between adjustment policies and growth in a small group of developing countries- Bangladesh, Chile, Ghana, India, Mexico, Morocco, Senegal, and Thailand - during 1970 -93. It provides an overview of the adjustment and growth experience, examines in depth several policy issues of particular interest, and distills the principal policy lessons for the design of adjustment policies.